Cenizas del futuro: nostalgia y ruinas en el relato cybernoir - Sanchez Blasco, Pablo (L'Atalante. Revista de estudios cinematográficos, 2023)
The cyber noir genre was born in 1982 with the release of Blade Runner (Ridley Scott, 1982), the first of many films to fuse the resources of classical film noir with dystopian science fiction. Since then, there have been numerous variants of this modality in which the investigations of the noir detective take place in a dehumanised world that raises questions about the goal of technological progress. Focusing on Blade Runner 2049 (Denis Villeneuve, 2017) and Reminiscence (Lisa Joy, 2021), this article analyses the current evolution of a genre influenced by the nostalgic obsession affecting Hollywood today. These are two films in which neo-noir’s nostalgia for its precursors is harmonised with a personal nostalgia represented by the detective’s exploration of the past. This analysis confirms that both films could be classified as a new form of the contemporary nostalgia film.